Examining the impact of youth centre attendance on self-reported mental health in Icelandic adolescents : a population based cross-sectional analysis - Svala Rún Magnúsdóttir 2002- (2024)
In Iceland, youth centres are places where children’s and adolescents’ well-being and development are supported. Youth centres therefore provide children with a place where they can socialize with their peers outside of school. Research indicates that participation in youth centres may have a positive impact on adolescents’ mental health, although there has been a lack of research regarding youth centres in Iceland specifically. In this study, the relationship between participating in youth centres and self-reported mental health was examined by using logistic regression and chi-square tests. Data was used from the survey "Youth in Iceland 2022" and participants in the study were Icelandic adolescents aged 8th-10th grade. In total, 57.5% of the participants in the study were participants in youth centres. The results of the study suggest that participation in youth centres is associated with increased odds of good mental health at certain levels. The findings also suggest that youth centres are important alternatives for a subgroup of students who do not participate in organized recreation. Keywords: adolescents, organized recreation, youth centres, mental health Á Íslandi eru félagsmiðstöðvar staðir sem stuðla að vellíðan og þroska barna og ungmenna. Félagsmiðstöðvar bjóða því unmennum upp á stað þar sem þau geta umgengist jafnaldra sína utan skólatíma. Rannsóknir benda til þess að þáttaka í félagsmiðstöðvum geti haft jákvæð áhrif á andlega heilsu ungmenna, en skortur hefur verið á rannsóknum er varða félagsmiðstöðvar á Íslandi sérstaklega. Í þessari rannsókn voru tengsl félagsmiðstöðva við andlega heilsu ungmenna rannsökuð með því að nota tvíkosta aðhvarfsgreiningu og kíkvaðratpróf. Gögn voru notuð úr könnunni „Ungt fólk og líðan 2022“ og voru þáttakendurnir íslensk ungmenni í 8.-10. bekk. Í heildina tóku 57.5% þáttakenda þátt í félagsmistöðvastarfi. Niðurstöður rannsóknarinnar sýndu fram á að þáttaka í félagsmiðstöðvum tengist auknum líkum á góðri andlegri heilsu. Niðurstöður rannsóknarinnar benda einnig ...